Effects of dietary supplementation with fish-derived Bacillus amyloliquefaciens AV5 on growth status, immune response, microbiota, and intestinal health of Nile tilapia (Oreochromis niloticus) - Vicent Michael Shija; Huapu Chen; Yi Li; Lishuko Ng’onga; Kwaku Amoah; Zhong Yong; Junxi Chen; Yu Dapeng; Robert Mkuye; Jia Cai (Aquaculture Reports)
In this study, the effects of the probiotic Bacillus amyloliquefaciens AV5 on Nile tilapia (Oreochromis niloticus) at three different concentrations (GC: 0 cfu/g feed, G1: 1 ×106 cfu/g feed, and G2:1 ×108 cfu/g feed) on growth conditions, antioxidant responses, microbiota, and intestinal structure were assessed. Nile Tilapia fingerlings (23.5 g ± 0.2 g) were provided with commercial feed containing different doses of B. amyloliquefaciens AV5 over 42 days. The results showed substantial improvements in initial weight, weight gain rate, survival rate, condition factor, intestinal somatic index, hepatosomatic index, and specific growth rate in the G2 group compared to the GC and G1 groups. However, the feed conversion ratios were notably higher in G1 and GC than in G2. Alkaline phosphatase and acid phosphatase activities increased considerably in G2 compared with GC and G1, but alanine aminotransferase and aspartate aminotransferase levels increased significantly in GC and G1 compared with G2. The most abundant bacteria at the phylum level are Proteobacteria, followed by Fusobacteriota, Actinobacteriota, Bacteroidetes, and Firmicutes. At the class level, there was a notably higher presence of Bacteroidia and Bacilli in groups G1 and G2 than in GC, indicating the potential suppression of harmful bacteria within the G1 and G2 diet groups. Improved intestinal morphology was observed in the G2 group. In G2, the fish livers changed from abnormally shaped to normally shaped nuclei and the gaps within the liver tissues decreased. These findings indicate that G2 can significantly enhance Nile tilapia growth.